The oscillating Mucin-type protein DPY-6 has a conserved role in nematode mouth and cuticle formation. Issue 3 (23rd December 2021) - Sun, Shuai; Theska, Tobias; Witte, Hanh; Ragsdale, Erik J; Sommer, Ralf J
Abstract: Nematodes show an extraordinary diversity of mouth structures and strikingly different feeding strategies, which has enabled an invasion of all ecosystems. However, nearly nothing is known about the structural and molecular architecture of the nematode mouth (stoma). Pristionchus pacificus is an intensively studied nematode that exhibits unique life history traits, including predation, teeth-like denticle formation, and mouth-form plasticity. Here, we used a large-scale genetic screen to identify genes involved in mouth formation. We identified Ppa-dpy-6 to encode a Mucin-type hydrogel-forming protein that is macroscopically involved in the specification of the cheilostom, the anterior part of the mouth. We used a recently developed protocol for geometric morphometrics of miniature animals to characterize these defects further and found additional defects that affect mouth form, shape, and size resulting in an overall malformation of the mouth. Additionally, Ppa-dpy-6 is shorter than wild-type with a typical Dumpy phenotype, indicating a role in the formation of the external cuticle. This concomitant phenotype of the cheilostom and cuticle provides the first molecular support for the continuity of these structures and for the separation of the cheilostom from the rest of the stoma. In Caenorhabditis elegans, dpy-6 was an early mapping mutant but its molecular identity was only determined during genome-wide RNAi screens and not further investigated. Strikingly, geometric morphometric analysis revealed previously unrecognized cheilostom and gymnostom defects in Cel-dpy-6 mutants. Thus, the Mucin-type protein DPY-6 represents to the best of our knowledge, the first protein involved in nematode mouth formation with a conserved role in cuticle deposition. This study opens new research avenues to characterize the molecular composition of the nematode mouth, which is associated with extreme ecological diversification. Abstract : Using the nematode Pristionchus pacificus, Sun, Theska et al . identify Ppa-dpy-6 to encode a Mucin-type protein involved in the specification of the anterior mouth part. Ppa-dpy-6 is shorter than wild-type with a Dumpy phenotype, indicating a role in cuticle formation. This concomitant phenotype of the cheilostom and cuticle provides the first molecular support for the continuity of these structures and for the separation of the cheilostom from the rest of the stoma.